EP-384 Surgical site infections: A prospective study of incidence and risk factors at a District General Hospital. (9th August 2022) - Patel, Maitreyi; Anad, Adam; Warrag, Ibrahim; Abidia, Ahmed
Abstract: Aims: To determine the incidence of surgical site infection (SSI)amongst patients undergoing general surgery between 1/10/2020 to 30/11/2020 and identify factors associated with SSI. Methods: Data of adult patients operated between October 10, 2020, and November, 2020 was prospectively collected. Southampton wound scoring was used for categorizing the wound complication. Patient data was collected using electronic patient records. Data were analyzed using Excel Microsoft 2016. Chi square and t-test were used for analysis as appropriate. P-value < 0.05 was considered statistically significant. Results: The overall incidence of SSI was 13.84% (22 out of 159 patients). The associated risk factors (p<.05) were found to be an increased age, pre operative haemoglobin <100, type of surgery, longer duration of surgery (> 2 h), post operative critical care admission and prolonged duration of hospital stay. Most patients (36%) had Southampton grade of III. They were all managed conservatively with antibiotics and dressing. Emergency surgery did not significantly increase risk of SSI. Conclusion: Our data suggests that these risk factors could be considered as indicators of SSI. Relevant strategies for targeting the at-risk patients to optimize the modifiable factors where feasible, would enable to decrease the incidence of surgical site infections. Emergency surgery did not significantly increase risk of SSI.